Factors influencing customer purchase behavior through purchase intention on green cosmetic products - Marbun, Nency; Rahmiati, Filda; Mangkurat, R. Stevanus Bayu; Ismail, Yunita (Institute for Advanced Science Social, and Sustainable Future, 2024)
Introduction: The cosmetic industry provides several plastic packaging problems for the environment. It has been shown that 120 billion units of packaging are produced annually by the global cosmetic industry. Campaigns for environmentally friendly cosmetic packaging products are growing. This study aims to determine the effect of plastic packaging on the environment. Methods: Research on environmentally friendly cosmetic products was conducted by distributing questionnaires through online platforms. The total questionnaire respondents were 215 Generation Z people, and the questionnaire was then analyzed with PLS-SEM. Findings: The results showed that personal norms have a significant effect both directly and mediated by green purchase intention on green purchase behavior. Conclusion: However, environmental concern does not have a significant effect, even though it has been mediated by green purchase intention on green purchase behavior in environmentally friendly cosmetic products in Indonesia. Novelty/Originality of this article: This study explores the factors influencing the purchasing behavior of eco-friendly cosmetic products among Indonesian Generation Z and reveals the critical role of personal norms in driving sustainable consumption. This study provides valuable insights for the cosmetic industry in developing effective marketing strategies for eco-friendly products.